Effectiveness of Flashcard on Knowledge and Attitudes of Iron Consumption in Women - Wati, Irna; Harumi, Ani Media; Prwanto, Triana Septianti; Sulistyowati, Dwi Wahyu Wulan (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2025)
During pregnancy, the need for iron is greatly increased to meet red blood cells in overcoming the problem of anemia in pregnant women. This study aims to determine the effectiveness of flashcards on knowledge and attitudes towards iron consumption in pregnant women. This type of research is a quasy experiment with a preset-postest design with control group design. The sample amounted to 32 which were selected using simple random sampling. Data collection using a questionnaire. Statistical tests used were Wilcoxon Sign Rank and Mann-Whitney U Test. The results showed that flashcards could increase knowledge from good to good (100%) and there was a change in attitude from good to fair (81.25%). This study concludes that learning media using flashcards is effective on the knowledge and attitude of iron consumption in pregnant women, in an interesting and easy-to-understand way. This flashcard media can help explain the concept of iron and anemia prevention, increase understanding and motivate pregnant women to have a healthy pregnancy.Keywords: Knowledge, Attitude, Flashcards, Iron Consumption